2012
DOI: 10.1111/j.1539-6924.2012.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposures from Chrysotile‐Containing Joint Compound: Evaluation of New Model Relating Respirable Dust to Fiber Concentrations

Abstract: The potential for fiber exposure during historical use of chrysotile-containing joint compounds (JCC) has been documented, but the published data are of limited use for reconstructing exposures and assessing worker risk. Consequently, fiber concentration distributions for workers sanding JCC were independently derived by applying a recently developed model based on published dust measurements from sanding modern-day (asbestos-free) joint compound and compared to fiber concentration distributions based on limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Recently, it was shown that collection of respirable dust samples for asbestos fiber analysis, to support exposure assessment, also was necessary to accurately estimate fiber concentrations of materials that are hygroscopic and constitute a “soft” matrix, such as joint compound. In such materials, larger nonrespirable particles collected as total dust can be broken into multiple smaller particles during sample collection, skewing fiber concentration estimates . Talcum powder provides a similar hygroscopic “soft” matrix when applied, often in more humid environments such as bathrooms where small particles tend to aggregate into larger particles that are outside of the respirable range.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was shown that collection of respirable dust samples for asbestos fiber analysis, to support exposure assessment, also was necessary to accurately estimate fiber concentrations of materials that are hygroscopic and constitute a “soft” matrix, such as joint compound. In such materials, larger nonrespirable particles collected as total dust can be broken into multiple smaller particles during sample collection, skewing fiber concentration estimates . Talcum powder provides a similar hygroscopic “soft” matrix when applied, often in more humid environments such as bathrooms where small particles tend to aggregate into larger particles that are outside of the respirable range.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we apply a semi‐empirical mathematical model to predict 8‐h TWA respirable dust concentrations from joint compound sanding activities . These predictions are coupled with an empirical factor that relates chrysotile asbestos fiber to respirable dust concentrations to predict 8‐h TWA asbestos fiber concentrations . We present data about time‐activity patterns of drywall construction, including finishing activities, obtained through a survey of drywall construction business owners and direct observation of drywall construction workers at active job sites.…”
Section: Introductionmentioning
confidence: 99%
“…(16) These predictions are coupled with an empirical factor that relates chrysotile asbestos fiber to respirable dust concentrations to predict 8-h TWA asbestos fiber concentrations. (17,18) We present data about time-activity patterns of drywall construction, including finishing activities, obtained through a survey of drywall construction business owners and direct observation of drywall construction workers at active job sites. These data are used to develop prototypical exposure scenarios for workers categorized according to their time-activity patterns and skill sets.…”
Section: Introductionmentioning
confidence: 99%
“…They used their results to derive a median conversion factor of 0.044 f/cm 3 per mg/m 3 respirable dust for sanding tasks and 0.025 f/cm 3 per mg/m 3 respirable dust for sweeping tasks (Sheehan et al 2011). Jones et al (2011) and Brorby et al (2012) developed mathematical models to estimate respirable dust exposures from sanding modern, asbestos-free joint compound products (Jones et al 2011;Brorby et al 2012). Jones et al measured personal and area respirable dust concentrations during the sanding of joint compound in an isolation chamber.…”
Section: Predictive Modelsmentioning
confidence: 99%
“…Brorby et al used published dust levels measured during the handling of modern day asbestos-free joint compound to estimate fiber concentrations during handling of historical asbestos-containing joint compound. The authors concluded that the fiber concentrations estimated with the new model were not significantly different from fiber concentrations measured during the historical use of asbestos-containing joint compound, for both enclosed and non-enclosed environments (Brorby et al 2012). Boelter et al (2015) calculated cumulative asbestos exposures for the sanding tasks performed by drywallers based on previously published survey data, direct field observations from contemporary construction worksites, and a semi-empirical mathematical model (Boelter et al 2015).…”
Section: Predictive Modelsmentioning
confidence: 99%